2015
DOI: 10.1111/phpp.12181
|View full text |Cite
|
Sign up to set email alerts
|

Black tattoos protect against UVR‐induced skin cancer in mice

Abstract: In UVR-irradiated black tattoos, remarkably, the development of UVR-induced skin cancer was delayed by the tattoos. Skin reflectance measurement indicated that the protective effect of black pigment in the dermis might be attributed to UVR absorption by black pigment below the epidermis and thereby reduction of backscattered radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 29 publications
0
34
0
2
Order By: Relevance
“…This was recently supported in a study on black tattoos and photocarcinogenicity in mice, which even indicated that light absorption in black tattoo pigment may delay the deve lopment of sun-induced skin cancer [27] .…”
Section: Discussionmentioning
confidence: 63%
“…This was recently supported in a study on black tattoos and photocarcinogenicity in mice, which even indicated that light absorption in black tattoo pigment may delay the deve lopment of sun-induced skin cancer [27] .…”
Section: Discussionmentioning
confidence: 63%
“…For further details, see the supplementary materials (for all online suppl. material, see www.karger.com/doi/10.1159/000468149) [13][14][15] .…”
Section: Methodsmentioning
confidence: 99%
“…By light and transmission electron microscopy (TEM) we aimed to clarify whether systemic distribution of the tattoo pigments to internal organs takes place. Using the same tattoo inks we have recently published results concerning photocarcinogenicity by recording skin tumours in mice [13,14] .…”
mentioning
confidence: 99%
“…Carcinogens may, over time, develop in the skin as a result of local metabolism and certainly, under the influence of the sun's ultraviolet radiation (UVR). Photochemical decomposition was, in a number of studies, shown to be relevant in relation to tattoo pigments, which are selective absorbers of light depending on their colours [6][7][8][9] . Photochemical breakdown products can undergo absorption and expose internal organs to new carcinogens parallel to the skin [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group studied the risk of skin cancer in mice after tattooing with the 2 commercial inks containing BaP and 2-anisidine, both inks banned from the Danish market in 2011 [9,13]. Studies included the combination of UVR and carcinogens.…”
Section: Introductionmentioning
confidence: 99%